2022
DOI: 10.1002/bio.4291
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tyramine in different types of food using novel green synthesis of ficus carica quantum dots as fluorescent probe

Abstract: Tyramine (TYM) is catecholamine releasing compound and TYM rich food causes hypertensive crisis due to a combination with monoamine oxidase inhibitor (MAOIs). Therefore, analysis of TYM in TYM rich food as (old cheese, cured meat, sausage, pickled olive and canned fish) and the environment is essential for hypertensive patients and to improvement of food industries. In this work, TYM was analyzed in different types of food using novel green synthesis carbon dots from Ficus carica (fig fruits). The gradual addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…S1 ( Supplementary Materials ). Besides, the powder X-ray diffraction (PXRD) image was utilized to study the formation of N@CQDs, the peak presented at 24.60 o is a diagnostic peak of carbon dots [ 13 , 15 ] as seen in Fig. S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 ( Supplementary Materials ). Besides, the powder X-ray diffraction (PXRD) image was utilized to study the formation of N@CQDs, the peak presented at 24.60 o is a diagnostic peak of carbon dots [ 13 , 15 ] as seen in Fig. S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the effect of temperature in the range of (25 – 60 o C) on relative fluorescence intensity (RFI) of N@CQDs was studied. Increasing temperature beyond 25 o C declined the fluorescence intensity [ 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quantum yield of B@CQDs was determined using the single point method [ 12 , 17 ]: where, Q st is quantum yield for standard solution (quinine sulphate), (I) is the integrated fluorescence intensity, is the refractive index of the water and A is absorption. B@CQDs have quantum yield 38.44%.Spectrophotometric and spectrofluorimetric equipment were used to analyses the quantum dots' spectrum properties.…”
Section: Resultsmentioning
confidence: 99%
“…The presented study provides varying advantages other than reported methods as the method is environmentally friendly, time saving, very simple and sensitive with a quantitative range from 4 to 100 ng mL −1 . Quantum dots is smart materials that have many applications as in industries, science, technology, and pharmaceutical analysis [ 12 14 ]. As a result, carbon quantum dots were used to analyze ELX in human plasma (pharmacokinetic assay), content uniformity, and then heteroatoms were introduced into carbon dots synthesis to fine-tune the conduction band position of doped CQDs, which led to the adjustment of the functions used to treat impurities and fluorescence of doped carbon dots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation